ASSESSMENT OF THE CONDITION OF THE PROCESSING INDUSTRY IN THE REPUBLIC OF KAZAKHSTAN - D.Tasbulatova (Academic Journal of Physical and Chemical Sciences, 2019)
The manufacturing industry plays the important role in the country’s economy, by stimulating innovation and increasing productivity, as well as improving the well-being of the population. Therefore, the creation of an effective structure of the processing industries is a permanent object of the active state-owned industrial Republic of Kazakhstan at the present stage. The article analyzes the state of development of the most important manufacturing industries in Kazakhstan. It is shown that the level of productivity in the manufacturing industry of Kazakhstan is 2 times lower than the average for the member countries of the Organization for Economic Cooperation and Development. The low level of availability of long-term credit resources, technological backwardness of production, and a shortage of qualified personnel have been identified as factors hindering the development of manufacturing industries. In addition, it was found that, despite the availability of agricultural raw materials, the agricultural raw materials processing sector is not sufficiently developed in Kazakhstan: Kazakhstan is import-dependent by 47% for processed types of food, and domestic enterprises of light industry provide only 20% of domestic consumption. To solve these problems, measures have been proposed to curb commodity exports, by introducing of high fees on the export of products with a low degree of processing and the provision of incentives to stimulate the export of products with high added value.